ASTI data promotes efficiency with merger of research institutions in Kenya - CGIAR Research Program on Policies, Institutions, and Markets (2017)
ASTI data contributed to justify the need for the merger of several institutions to form to the Kenya Agriculture and Livestock Research Organization (KALRO), for improved efficiency, capacity, technology adoption, and research outputs.